The Number of Macrophages and Heterophils on Chick Embryo Chorioallantoic Membrane After Gynura procumbens (Lour) Merr Extract Treatment and bFgF Induction - Hamid, Iwan Sahrial; P, Yuseni Kusuma; Bijanti, Retno; Aksono, E Bimo (Indonesian Journal of Cancer Chemoprevention, 2012)
Antiangiogenesis (inhibition of new blood vessels formation) has become a strategy to inhibit cancer development. The aim of this experiment was to investigate antiangiogenic effect  of  Gynura  procumbens  (Lour)  Merr  focusing  on  the  decreasing  of  the  number  of macrophages  and  heterophils  on  chick  embryo  chorioallantoic  membrane.  Nine-days-aged-eggs  were  divided  into  six  groups  (eight  eggs  each  group).  Group  I  (positive  control)  eggs were  induced  with  bFGF+Tris  HCl.  Group  II  (negative  control)  eggs  were  treated  with DMSO+Tris  HCl.  Group  III  (treatment  I)  eggs  were  induced  with  60  ng  bFGF  and  treated with  ethanolic  extract  of  G.  procumbens  leaves  with  the  dose  of  60  µg.  The  following treatment  groups,  i.e.  group  IV  (treatment  II),  group  V  (treatment  III),  and  group  VI (treatment IV) were treated with increasing dose of extract, starting from 75 µg, 90 µg, and the last was 110 µg. Eggs were incubated until they reach the age of twelve days to observe macrophages, while  to observe heterophils, eggs were incubated until  the  age of seventeen days. Based on haematoxylin-eosin staining, macrophages in the treatment groups were less than the control positive group (bFGF+Tris HCl), but based on giemsa staining, the effect of Gynura procumbens  in decreasing the number of heterophils could not  be observed  because some blood smears. These analysis suggest that  the  ethanolic extract of  Gynura procumbens leaves can perform as antiangiogenic agent decreasing the number of macrophages.Keywords: antiangiogenic, macrophages, heterophils, Gynura procumbens